Coughing in dogs: what is the evidence for and against a cardiac cough?. (16th January 2019) - Ferasin, L.; Linney, C.
Abstract : Cough has been historically reported as a major clinical sign of cardiogenic pulmonary oedema in dogs. However, recent evidence appears to contradict the traditional dogmatic approach that linked cough to congestive heart failure in dogs. Here we use a question‐based format to introduce and discuss the modern evidence regarding "cardiac cough" and the interpretation of this important but often misleading clinical sign.